2018
DOI: 10.4317/jced.55227
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the effect of impression materials and trays on the accuracy of angulated implants impressions

Abstract: BackgroundVinyl Polyether Siloxane is a newly introduced impression material and studies on that is scarce. Implant insertion in posterior mandible might be angulated due to anatomical considerations. The purpose of this study was to compare the dimensional and angular accuracy of impressions using full-arch versus sectional tray and Vinyl Polysiloxane versus Vinyl Polyether Siloxane in angulated implants.Material and MethodsFour implants were placed in dental areas #19, #21, #28 and #30 of a Kennedy class I m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A marginal numerical advantage was observed for VPES over PVS. Siadat et al (12,13) observed a smaller discrepancy for VPES and suggested it as a material of choice for direct and indirect impression techniques Higher tensile strength and better flow properties of VPES can make it more advantageous and preferred to other impression materials. Baig et al (11) determined that the accuracy of the VPES impression material was comparable with that of PE for multi-implant abutment level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A marginal numerical advantage was observed for VPES over PVS. Siadat et al (12,13) observed a smaller discrepancy for VPES and suggested it as a material of choice for direct and indirect impression techniques Higher tensile strength and better flow properties of VPES can make it more advantageous and preferred to other impression materials. Baig et al (11) determined that the accuracy of the VPES impression material was comparable with that of PE for multi-implant abutment level.…”
Section: Discussionmentioning
confidence: 99%
“…Fit precision depends on many factors, among which the impression and an accurate master cast are vital components (6). The factors that influence the cast accuracy are the characteristics of the impression material, technique, type of tray, die material, implant angulation, and fit tolerance between the implant components and transfer copings (7)(8)(9)(10)(11)(12). In the case of multiple implants, the quality of the final impression and transfer of the exact positions of the implants to the model are of utmost importance (13).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the measurement of dimensional accuracy and coefficient of variation displayed a significant difference in the assessment, thereby concluding that the closed tray technique produces a more dimensionally accurate impression with a lower coefficient of variation than the open tray technique. (5,8,9,2) Yet another in vivo comparative research study was conducted by Gallucci GO et al in 2011 to compare the accuracy outcomes of the open tray and closed tray impression techniques in partially edentulous patients treated with implants. The study measured the outcomes subjectively and objectively.…”
Section: Open Tray Versus Closed Tray Techniquementioning
confidence: 99%
“…Studies reported the addition-type silicones as one of the most dimensionally accurate materials for making impression. [ 12 13 ] Owing to the recent improvements in impression materials, dimensional accuracy is currently more dependent on the adopted impression technique rather than the material itself. [ 7 12 ] Nonetheless, some studies have claimed that the impression technique has no impact on the dimensional accuracy of impressions.…”
Section: Introductionmentioning
confidence: 99%